Frequency # 1 Toefl vocabulary : (Tổng hợp Thành phố Hồ Chí Minh, 2011)
The number of vocabulary questions given on the TOEFL has also increased drastically, and these questions now constitute approximately one third of all the questions on the reading section. A typical passage contains 4 vocabulary questions out of 13-14 questions in total. Considering that the reading section contains 3 or 5 reading passages, test takers will have to answer 12-20 vocabulary questions on the new iBT